A time-driven activity-based costing model to improve health-care resource use in Mirebalais, Haiti. (27th April 2015) - Mandigo, Morgan; O'Neill, Kathleen; Mistry, Bipin; Mundy, Bryan; Millien, Christophe; Nazaire, Yolande; Damuse, Ruth; Pierre, Claire; Mugunga, Jean Claude; Gillies, Rowan; Lucien, Franciscka; Bertrand, Karla; et al.
Abstract: Background: In resource-limited settings, efficiency is crucial to maximise resources available for patient care. Time driven activity-based costing (TDABC) estimates costs directly from clinical and administrative processes used in patient care, thereby providing valuable information for process improvements. TDABC is more accurate and simpler than traditional activity-based costing because it assigns resource costs to patients based on the amount of time clinical and staff resources are used in patient encounters. Other costing approaches use somewhat arbitrary allocations that provide little transparency into the actual clinical processes used to treat medical conditions. TDABC has been successfully applied in European and US health-care settings to facilitate process improvements and new reimbursement approaches, but it has not been used in resource-limited settings. We aimed to optimise TDABC for use in a resource-limited setting to provide accurate procedure and service costs, reliably predict financing needs, inform quality improvement initiatives, and maximise efficiency. Methods: A multidisciplinary team used TDABC to map clinical processes for obstetric care (vaginal and caesarean deliveries, from triage to post-partum discharge) and breast cancer care (diagnosis, chemotherapy, surgery, and support services, such as pharmacy, radiology, laboratory, and counselling) at Hôpital Universitaire de Mirebalais (HUM) in Haiti. The team estimated the direct costs of personnel, equipment, and facilities used in patient care based on the amount of time each of these resources was used. We calculated inpatient personnel costs by allocating provider costs per staffed bed, and assigned indirect costs (administration, facility maintenance and operations, education, procurement and warehouse, bloodbank, and morgue) to various subgroups of the patient population. This study was approved by the Partners in Health/Zanmi Lasante Research Committee. Findings: The direct cost of an uncomplicated vaginal delivery at HUM was US$62 and the direct cost of a caesarean delivery was US$249. The direct costs of breast cancer care (including diagnostics, chemotherapy, and mastectomy) totalled US$1393. A mastectomy, including post-anaesthesia recovery and inpatient stay, totalled US$282 in direct costs. Indirect costs comprised 26–38% of total costs, and salaries were the largest percentage of total costs (51–72%). Interpretation: Accurate costing of health services is vital for financial officers and funders. TDABC showed opportunities at HUM to optimise use of resources and reduce costs—for instance, by streamlining sterilisation procedures and redistributing certain tasks to improve teamwork. TDABC has also improved budget forecasting and informed financing decisions. HUM leadership recognised its value to improve health-care delivery and expand access in low-resource settings. Funding: Boston Children's Hospital, Harvard Business School, and Partners in Health.